Detection of Garlic Powder Adulteration Using FTIR Spectroscopy and Chemometrics: A Case Study in an Indonesia Marketplace - Elvira, Avika Rizky; Putri, Anggita Rosiana; Muchlashi, Luthfi Ahmad (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2024)
Garlic is a plant with numerous benefits, including its use as a culinary ingredient and for medicinal purposes. However, the rising demand does not align with the availability of garlic in Indonesia, resulting in high garlic prices. Excessively high prices may potentially lead to garlic powder adulteration. The objective of this study is to determine whether there are garlic powder products adulterated with maltodextrin in the Marketplace. A total of 10 garlic powder samples were purchased on Marketplace. The study utilized a combination of FTIR spectroscopy with chemometrics. The chemometrics employed in this study were OPLS-DA (Orthogonal Partial Least Squares Discriminant Analysis) for sample grouping, as well as PLS (Partial Least Squares) for multivariate calibration. The findings revealed that OPLS-DA could effectively group the samples. Additionally, the best multivariate calibration model (PLS) was obtained at the wavenumber range of 679-440 cm-1 with a calibration R2 value of 0.9981, RMSEC value of 1.11, validation R2 value of 0.9926, and RMSEP value of 2.12. Based on the research results, it was found that three products were not pure garlic powder, with details indicating two products containing maltodextrin as an adulterant and one product containing a non-maltodextrin adulterant.